Assessment of non-traumatic vertebral fractures in Cushing's syndrome patients - YAVUZ, DİLEK; APAYDIN, TUĞÇE (SPRINGER, 2021)
Purpose Hypercortisolism has detrimental effects on bone metabolism with the consequences of bone loss and bone fractures. We aimed to evaluate the frequency of vertebral fragility fractures and to determine the factors associated with Cushing's syndrome (CS). Methods A total of 135 patients diagnosed with Cushing's syndrome [108 patients with Cushing's disease and 27 patients with adrenocortical adenoma] and 107 healthy controls were included in this cross-sectional study. The available clinical, laboratory, and radiologic data of patients with CS were recorded, retrospectively. Lateral vertebral radiograms were evaluated for vertebral fragility fractures according to Genant's semi-quantitative method. Bone mineral density (BMD) was determined using a Dual-energy X-ray absorptiometry (DEXA). Results Vertebral fragility fractures (VFs) were observed in 75.3% (n = 61) of the patients. The median number of VFs was six (min-max: 2-12). All patients with vertebral fractures had thoracic VF, and 50.7% of the patients had lumbar fragility fractures. Thirty-three (40.7%) patients with vertebral fractures had normal bone densitometry values. Osteoporosis and osteopenia were observed in 16.2% and 40.7% of the patients, respectively. The duration of active disease, the presence of ACTH-secreting pituitary adenoma, and 24-h urinary cortisol did not influence the presence of vertebral fractures. Vertebral fractures were independently associated with age, FSH, LH levels, and lumbar BMD (R-2 = 68.18%, p = 0.028). The femoral neck BMD (but not lumbar BMD) was independently associated with age, BMI, and PTH levels (R-2 = 48.48%, p < 0.001). Conclusion Vertebral fracture frequency was higher in CS patients. Most of the patients with vertebral fractures had multiple fractures. Although low lumbar BMD was associated with VF, patients with CS with normal bone densitometry could experience VF. Vertebral radiograph evaluations as a part of routine evaluation for silent vertebral fractures may help to prevent further fractures in patients with CS.
Keywords: Cushing syndrome; Bone loss; Pathologic fractures; Osteoporosis; BONE-MINERAL DENSITY; SURGICAL CURE; ADULT PATIENTS; MASS; NORMALIZATION; OSTEOPOROSIS; RECOVERY; TURNOVER; DISEASE